Bissu sebagai Pemimpin Adat Pernikahan: Kajian Tentang Warisan Budaya Masyarakat di Desa Bontomatene Kecamatan Segeri Kabupaten Pangkep - Jufri, Hidayat Dwitama; Nuraeni S; Arif, Muhammad; Yani, Ahmad; Habib Akramullah, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2023)
The Role of Bissu in the Wedding Customs of the Bugis Community, Sigeri District, Pangkep Regency. So the research objective that can be achieved is to describe the role of Bissu in the wedding customs of the Bugis community, Sigeri District, Pangkep Regency. This research uses historical, anthropological, sociological and religious approaches. Bissu in Bugis society, especially in Sigeri District, Pangkep Regency, has an important role and has a high status. Bissu's role before the arrival of Islam in South Sulawesi was as a spiritual advisor, such as when carrying out mass planting involving many people. Bissu will be asked to determine the right time to start, and Bissu is also the link between humans and the gods, as well as the people and the king. Bissu certainly has other roles in various customs, especially weddings in the community in Bontomatene Village, Pangkep Regency. Bissu's many roles in wedding customs are not only Indonesian botting, each stage of Bissu marriage has a role such as Ma'manu' manu', Mappasierekeng, Mappasili', Mappacci, Mappenre Botting.